Simultaneous Determination and Stability Test of Two Phthalic Anhydride Derivatives, Senkyunolide A and Z‐Ligustilide, in the Water Extract of Cnidium Rhizome from Different Geographical Regions and Species Using HPLC‐UVD Analysis. (10th May 2018) - Jang, Hyeon Seok; Kang, Kyo Bin; Yoo, Guijae; Kwon, Euna; Yun, Jun‐Won; Kang, Byeong‐Cheol; Hong, In Kee; Kim, Seung Hyun; Sung, Sang Hyun; Cho, Hyun‐Jong; Jang, Young Pyo; Yang, Heejung
Abstract : Cnidium rhizome from Cnidium officinale Makino and Ligusticum chuanxiong Hort (Umbelliferae) is traditionally used to treat pain in East Asian countries. Senkyunolide A and Z ‐ligustilide are phthalic anhydride derivatives that are the bioactive components of cnidium rhizome and chemical markers of the two species; they are also susceptible to external stimuli. In this study, we developed a method to identify two chemical markers using high‐performance liquid chromatography (HPLC) with an ultraviolet detector (UVD); the contents of senkyunolide A and Z ‐ligustilide in cnidium rhizome from different regions were quantified. The stabilities of the compounds were tested at two different temperatures over 12 months. An HPLC‐UVD system was used to identify and quantify senkyunolide A and Z‐ligustilide in 10 C. officinale samples and 6 L. chuanxiong samples from China and Korea. The long‐term stability of the C. officinale samples in dark conditions at 4 and 25 °C was also tested. The calibration curves for the two chemical markers showed high linearity (R2 = 1.0000), the precision was high (relative standard deviation (RSD) <4.17%), and the recoveries were within the range of 95–105%. The contents were mostly independent of the geographical origin and species, and >10% of the compounds degraded after storage at 4 and 25 °C for 6 months. A method was developed to rapidly identify two chemical markers in cnidium rhizome with good linearity, precision, and accuracy using HPLC‐UVD. These markers will be utilized for the quality control or evaluation of herbal preparations containing cnidium rhizome. Abstract :